Christians in Persia (RLE Iran A). - Waterfield, Robin (Routledge Library Editions: Iran., 2012)
"When it was originally published this book broke new ground in presenting one continuous narrative of the history of Christians in Persia from the second century A.D to the 1970s. The material gathered here was previously only to be found in obscure books, manuscripts and foreign periodicals. Christians in Persia shows the intricate history of the period concerned; the personalities of the rulers and the ruled; the difficult task of the missionaries; their successes and failures and the consequences of their efforts. All this is related to the wider history of the country and to the expansion of Christianity in the East." --